2021
DOI: 10.1159/000518346
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Extracorporeal Membrane Oxygenation Patients: National Analysis of Impact of Age

Abstract: <b><i>Background:</i></b> The aim of this study was to determine epidemiology and outcomes of acute kidney injury (AKI) in patients on extracorporeal membrane oxygenation (ECMO) and to assess if age modifies the effect of AKI on mortality. <b><i>Methods:</i></b> Using National (Nationwide) Inpatient Sample Database for hospitalizations in the USA from 2003 to 2014, we identified adult patients on ECMO support. Using International Classification of Diseases 9th Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses. Of multivariate analyses, diverse populations, compared with nondiverse/White patients, were independently associated with mortality (26, 27, 29, 30, 32, 35, 85–100), adverse neurologic outcomes (101), or prolonged ECMO duration (34).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, 54 studies (58%) found no statistical association between race and/or ethnicity and outcome (37–76), while 36 (39%) observed adverse outcomes in populations from underrepresented/diverse racial or ethnic backgrounds (Black/African American, Asian, Hispanic, or “other”/“non-Caucasian”/“non-White”). Of citations identifying adverse outcomes, 8 (22%) used univariate (77–84) and 28 (78%) used multivariate analyses. Of multivariate analyses, diverse populations, compared with nondiverse/White patients, were independently associated with mortality (26, 27, 29, 30, 32, 35, 85–100), adverse neurologic outcomes (101), or prolonged ECMO duration (34).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%